Catalytic c−h activation of hydrocarbons by rhodium(I) and iridium(I) complexes with hemilabile quinolyl-cp ligands - Kohl, Gerald; Rudolph, Ralph; Pritzkow, Hans; Enders, Markus (Organometallics, 2005)
The rhodium(I) and iridium(I) complexes 3a−6a contain the hemilabile Cp-quinoline chelate ligands 1 and 2, respectively, where the hard nitrogen donor does not displace the good acceptor ligand ethylene. After irradiation with visible light, intensely colored complexes are obtained, where the N-donor coordinates to the metal centers. Depending on the metal atom and on the substitution pattern at the Cp rings, the mono-ethene complex with N-metal coordination can be observed spectroscopically (e.g., 3b) or C−H addition products are probable intermediates. The iridium complex 6a is able to activate the aliphatic C−H bond in cyclohexane. With the rhodium complex 5a as the precatalyst, catalytic H/D exchange reactions have been performed with olefinic substrates. With linear α-olefins a fast double-bond isomerization dominates. The hemilabile ligands stabilize the catalytically active metal complexes without suppressing their activity significantly.